A Surgical Cryoprobe for Targeted Transcorneal Freezing and Endothelial Cell Removal. (16th May 2017) - Akhbanbetova, Alina; Nakano, Shinichiro; Littlechild, Stacy L.; Young, Robert D.; Zvirgzdina, Madara; Fullwood, Nigel J.; Weston, Ian; Weston, Philip; Kinoshita, Shigeru; Okumura, Naoki; Koizumi, Noriko; Quantock, Andrew J.
Abstract : Purpose . To examine the effects of transcorneal freezing using a new cryoprobe designed for corneal endothelial surgery. Methods . A freezing console employing nitrous oxide as a cryogen was used to cool a series of different cryoprobe tip designs made of silver for high thermal conductivity. In vitro studies were conducted on 426 porcine corneas, followed by preliminary in vivo investigations on three rabbit corneas. Results . The corneal epithelium was destroyed by transcorneal freezing, as expected; however, the epithelial basement membrane remained intact. Reproducible endothelial damage was optimally achieved using a 3.4 mm diameter cryoprobe with a concave tip profile. Stromal edema was seen in the pre-Descemet's area 24 hrs postfreeze injury, but this had been resolved by 10 days postfreeze. A normal collagen fibril structure was seen 1 month postfreeze, concurrent with endothelial cell repopulation. Conclusions . Transcorneal freezing induces transient posterior stromal edema and some residual deep stromal haze but leaves the epithelial basement membrane intact, which is likely to be important for corneal re-epithelialization. Localized destruction of the endothelial monolayer was achieved in a consistent manner with a 3.4 mm diameter/concave profile cryoprobe and represents a potentially useful approach to remove dysfunctional corneal endothelial cells from corneas with endothelial dysfunction.